“NASH-Worldwide the Commonest Aetiology of Liver Cirrhosis”- a Review Article - Jannat, Syeda Nur E; Islam, M M Shahin Ul; Haque, Mohammad Majharul; Imam, Iftekhar; Ahmed, Dewan Saifuddin (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
NAFLD is defined by the presence of fat in the liver (>5% hepatocytes show macrovesicular steatosis) without evidence of other causes of fat accumulation in the liver such as alcohol use (< 20 g/d for women and <30 g/d for men), hepatitis C or certain medications. The spectrum of disease includes NAFL, NASH, cirrhosis and HCC. Disease progression depends on stages of fibrosis. Patients are usually referred with incidentally noted hepatic steatosis on imaging or elevated liver enzymes. Although liver biopsy is the gold standard for diagnosis but worldwide it’s much under practiced and several non invasive tests are currently recommended to identify at risk NASH (≥ stage 2 fibrosis) or advance fibrosis who are at highest risk of developing to cirrhosis. Screening in high-risk populations - T2DM, obesity with metabolic complications, a family history of cirrhosis or significant alcohol use allows for interventions that may prevent future hepatic complications. Currently, about 38% of the global population has a diagnosis of NAFLD. The incidence of hepatic decompensation, HCC and death related to NASH cirrhosis are expected to increase 2-to 3-fold by 2030. NASH- cirrhosis is already the leading indication of liver transplantation worldwide. Currently no specific treatments is licensed for NASH, lifestyle modification and exercise, primarily weight loss is the key to management. The rising clinical and economic burden of NAFLD has highlighted the need for a streamlined approach to prevention, diagnosis, and treatment of the disease that has been discussed in this narrative review. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(2):112-126.